Dermatological manifestations of COVID-19 and its therapies: a review - Singdia, Heena; Mathur, Rachita; Nijhawan, Shivi; Rani, Neha; Kothari, Deepika; Garg, Rohit; Bhargava, Puneet; Mathur, Deepak K. (International Journal of Research in Dermatology, 2021)
In the beginning of the COVID-19 pandemic when we were still getting used to the rising cases every day and limited resources to deal them with, the focus was to get a hold of the situation as quickly as possible. Seven months into the pandemic, the cases are still on the rise but we have gathered some knowledge through the researches getting published every day, most of which are focused on the involvement of respiratory system, cardiovascular system, central nervous system, and gastrointestinal system. Dermatological manifestations have not been given their due importance. Lately, many patients have started presenting with dermatological manifestation sometimes preceding or sometimes during COVID-19 infection with or without involvement of other systems. This may be beneficial to clinicians all over the world, to determine potential dermatological signs in COVID-19 and also help in earlier suspection of the COVID-19 infection. Many cutaneous adverse drug reactions (ADR) to drugs advocated in COVID-19 treatment are also being reported every day, which are discussed in this review. Here we attempt to review dermatological manifestations of COVID-19 infections and drug reactions by the drugs advocated for its treatment and an understanding in its path mechanisms reported thus far. This will help clinicians to get an insight into what to expect and when to expect in terms of dermatological manifestation of COVID-19 and its drugs.